Assessment of Anxiety and Depression and its Association with Socio-demographic Characteristics among Family Caretakers of Cancer Patients - Khalid Hussain; Tanseer Ahmed; Amjad Ali; Faheem Raza (Aziz Fatimah Medical and Dental College, 2021)
Objective: To find out the frequency of anxiety and depression and its association with socio-demographics characteristics among family caretakers of cancer patients. Methodology: This descriptive cross sectional study of 300 participants was carried out at Dr. Ruth K.M Pfau Civil Hospital and Dow University Hospital, Karachi from December 01, 2020 to January 30, 2021. Before the study ethical approval was taken. The Aga Khan University Anxiety and Depression Scale (AKU-ADS) was used to assess the symptoms among family caregivers of cancer patients. The inclined adult male and female family members of cancer patients who were admitted in Dow University Hospital and Dr. Ruth K.M. Pfau Civil Hospital Karachi was included in this study.  The data was analyzed by using SPSS version -21. Frequency analy- sis was performed for demographic variables and chi-square test was also run to check the association of anxiety and depression with socio-demographic characteristics of study participants. Results: Finding of this study revealed that 39% of participants were having anxiety and depression. We found that gender, marital status, age group, educational level and patient's relationship showed significant p value of <0.001 with anxiety and depression. Conclusion: This study concludes that approximately one third of the study participants suffered from anxiety and depression. The demographic variables contributing to anxiety and depression include age, gender, and marital status, relationship with patient and educational level of the participants.